ANALISIS KINERJA RUAS JALAN TERHADAP U-TURN DI KOTA PEKANBARU - Husni, Husni Mubarak; Basri, Doni Rinaldi; Octiriani, Delka (Civil Engineering Scientific Journal, 2023)
ABSTRACT: As a result of the closure of the U-Turn, the people around Jalan HR. Soebrantas complained because the travel time they took was very long and there was a buildup of vehicles at the U-Turn intersection of Jalan Manggis. The problem in this study is how is the condition of the U-Turn in front of the handsome Nurul Huda Mosque today . and how to overcome the U-Turn delay in front of the Nurul Huda Mosque . The method used in this study is analysis of existing traffic performance, analysis of traffic performance, applying 3 alternatives , proposing alternative problem solving, alternative problem solving based on the results of HR Road Performance Comparison. Soebrantas, it is obtained that the average degree of road saturation is 0.80, and the service level is D: The flow is approaching unstable, the speed is still tolerable. Alternative 2, the solution to the problem for this research, namely by widening the road in front of the shops This plan affects traffic performance to run smoothly as happened on the Purwodadi road section, but this is still hampered due to land acquisition if it is carried out along the HR road. Soebrantas. Alternative 3, using vissim simulation for U-Turn closure This plan is the final plan, but if this plan is carried out, you must plan for a Fly Over at the Tobek Godang red light intersectionKeywords: Alternative , U-Turn, Road performanceABSTRAK: Akibat dari penutupan U-trun membuat masyarakat sekitar jalan HR.Soebrantas yang mengeluh dikarenakan waktu tempuh yang mereka jalani sangat lama dan terjadi penumpukan kendaraan disimpang U-Turn Jalan Manggis. Adapun permasalahan dalam penelitian ini adalah Bagaimana kondisi U-Turn  depan Masjid Nurul Huda tampan saat ini. dan Bagaimana cara untuk mengatasi waktu tundaan U-Turn depan Masjid Nurul Huda. Metode yang digunakan dalam penelitian ini Analisis Kinerja lalulintas Exsisting, Analisis kinerja lalulintas, menerapkan 3 Alternatif , Usulan Alternatif Penyelesaian Masalah, alternatif pemecahan masalah Berdasarkan hasil Perbandingan Kinerja Jalan HR. Soebrantas, maka didapatkan rata-rata derajat kejenuhan jalan menjadi 0,80, dan tingkat pelayanan menjadi D: Arus mendekati tidak stabil, kecepatan masih dapat di tolerir. Alternatif 2,  pemecaah masalah untuk penelitian ini , yakni dengan membuka pelebaran jalan di depan pertokoan Rencana ini mempengaruhi kinerja lalu lintas menjadi lancar seperti yang terjadi pada ruas jalan purwodadi , namun hal ini masih terhambat akibat pembebasan lahan jika dilakukan di sepanjang jalan HR. Soebrantas. Alternatif 3, menggunakan simulasi vissim untuk penutupan U-Turn Rencana ini adalah rencana terakhir namun jika rencana ini dilakukan harus merencanakan Fly Over di simpang lampu merah Tobek GodangKata kunci: Alternatif , U-Turn, Kinerja jalan